Screening chemical libraries for nucleic-acid-binding drugs by in vitro selection: a test case with lividomycin - Lato, S M; Ellington, A D (Molecular diversity, 1996)
Screening new drugs is a costly and time-consuming process. Identifying new targets for existing therapeutics is often a particularly effective avenue for drug development. We have investigated whether in vitro selection can be used for target acquisition. Aminoglycoside antibiotics are known to bind to and inactivate functional natural nucleic acids, such as ribosomal RNA. As an example of how new targets for aminoglycosides could be identified, a lividomycin aptamer was iteratively isolated from a random sequence pool. The consensus sequence of this and other anti-aminoglycoside aptamers was used as the basis for a comprehensive search of natural sequence databases. Surprisingly, a high degree of similarity was found between aptamers and genomic sequences from a variety of organisms. While many of the similarities found are in regions of unknown or nonessential function, some of the sequences are found in critical genes in pathogenic organisms.